Exploration of a calcium–organic framework as an anode material for sodium-ion batteries. Issue 64 (21st July 2016) - Zhang, Yan; Niu, Yubin; Wang, Min-Qiang; Yang, Jingang; Lu, Shiyu; Han, Jin; Bao, Shu-Juan; Xu, Maowen
Abstract : In this communication, we designed and synthesized a novel calcium–organic framework and presented it as an anode material for sodium-ion batteries. Abstract : In this communication, we designed and synthesized a novel calcium–organic framework and presented it as an anode material for sodium-ion batteries. The results show that it delivers a reversible capacity of higher than 140 mA h g −1 even after 300 cycles. The remarkable performance is attributed to the high structural stability and extremely low solubility of the calcium–organic framework in electrolytes.